Leadership is not a dirty word : exploring and embracing leadership in ECEC - Arna H. Jónsdóttir 1953-; Hard, Louise (European Early Childhood Education Research Journal, 2013)
Leadership continues to be an energetically debated and contentious concept. In many contexts it elicits heated and robust discussion and illustrates a degree of disenchantment with the enactment of leadership by corporate moguls, politicians and others in positions of leadership responsibility (Wheatley, M. 2005. Finding Our Way: Leadership for Uncertain Times. San Francisco: Berrett-Koehler Inc; Sinclair, A. 2007. Leadership for the Disillusioned: Moving Beyond Myths and Heroes to Leading that Liberates. Sydney: Allen and Unwin; Preskill, S., and D. Brookfield. 2009. Learning as a Way of Leading: Lessons from the Struggle for Social Justice. San Francisco: John Wiley & Sons). This was clearly illustrated in the 2008 Icelandic economic context where the community was turned upside down due to adventurous ‘entrepreneurs’, who, within a defective surveillance system, caused the collapse of the bank and financial system. In contrast leadership in the field of early childhood education could be expected to reflect aspects connected to the stereotypically feminine leadership style and demonstrate a collaborative or team approach, participation and power sharing (Shakeshaft, C. 1989. Women in Educational Administration. Newbury Park, CA: SAGE; Strachan, J. 1993. “Including the Personal and the Professional: Researching Women in Educational Leadership.” Gender and Education 5 (1): 71–80). However, this article explores two studies of leadership in the field of early childhood education and care (ECEC), one conducted in Iceland and the other in Australia and findings illustrate aspects such as micro-politics and horizontal violence which emerge as powerful influences on leadership aspirations and enactment.